? - open sets and a new class of functions - Caldas, Miguel; Jafari, Saeid; Latif, R. M. (Pro Mathematica, 2009)
The concept of (b, s)-continuous functions in topological spaces is introduced and studied. Some of their characteristic properties are considered. Also we investigate the relationships between these classes of functions and other classes of functions.